Adriatic weather : meteorology for sailors - Vučetić, Marko (Array, 2013)
Sadržaj: 1. Weather systems (Cyclones, Anticyclones, What the barometers says) ; 2. The wind and the sea (Winds during stable weather, The third quadrant - the ships' graveyard, The Bura - an Adriatic phenomenon, The Jugo, The winter Levantra, Wind calendar) ; 3. Special situations in the Adriatic (Adriatic thunderstorms, Waterspouts, Temperature, Precipitation, September tranquillity, Fog and mist at sea) ; 4. Local weather signs ; 5. The diversity of the adriatic climate (Istria, Cres and Lošinj, The climate of Krk and Rab, The island of Pag, The Zadar islands, Cape Ploča - Šibenik, Manios bay, Neretva, Dubrovnik waters, The open Adriatic sea, Dangers) ; 6. Weather reports and forecasts ; 7. Beyond the strait of Otranto